2021
DOI: 10.1038/s41419-021-03661-4
|View full text |Cite
|
Sign up to set email alerts
|

MCPIP1-mediated NFIC alternative splicing inhibits proliferation of triple-negative breast cancer via cyclin D1-Rb-E2F1 axis

Abstract: Triple-negative breast cancer (TNBC) is the most aggressive subtype with the worst prognosis and the highest metastatic and recurrence potential, which represents 15–20% of all breast cancers in Chinese females, and the 5-year overall survival rate is about 80% in Chinese women. Recently, emerging evidence suggested that aberrant alternative splicing (AS) plays a crucial role in tumorigenesis and progression. AS is generally controlled by AS-associated RNA binding proteins (RBPs). Monocyte chemotactic protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…Thus, the exploration of potential prognostic biomarkers is urgently required for the guidance of the individualized treatment and management of BC patients. As a kind of protein that can function via interaction with target RNAs, multiple RBPs have been found to be dysregulated and relevant to the prognosis of BC patients [ 44 , 45 , 46 ]. Furthermore, the prognostic signature constructed by three RBPs has also been established in BC [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the exploration of potential prognostic biomarkers is urgently required for the guidance of the individualized treatment and management of BC patients. As a kind of protein that can function via interaction with target RNAs, multiple RBPs have been found to be dysregulated and relevant to the prognosis of BC patients [ 44 , 45 , 46 ]. Furthermore, the prognostic signature constructed by three RBPs has also been established in BC [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result could partially explain why the bc-GenExMiner database indicated a high rate of lymph node metastasis in patients with high PPP1CA expression. In addition, PPP1CA can bind to cyclin D1 to phosphorylate RB [ 29 ] or can dephosphorylate breast cancer susceptibility protein-1 (BRCA1) [ 30 ], all of which induce cell cycle deregulation and promote tumor cell proliferation. Therefore, inhibition of PPP1CA may play an important role in inhibiting breast cancer proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported DCAF3, a novel RBP, promoted TNBC metastasis by binding to and accelerating the degradation of DTX3 [ 25 ]. Chen et al showed MCPIP1, a zinc finger RBP, suppressed the proliferation of TNBC by mediated NFIC alternative splicing [ 26 ]. To clarify the exact RBP in nuclear EGFR-mediated cancer progression, we evaluated the clinical value of those RBPs in TNBC and found NONO was significantly upregulated in TNBC and closely associated with breast cancer malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown that RBPs are involved in various important biological processes [ 24 ]. Moreover, recent studies have identified RBPs play a critical role in TNBC [ 25 , 26 ], but the underlying mechanisms and clinical significance of the vast majority of RBPs in TNBC remain unknown. Here, we observed non-POU domain-containing octamer-binding protein (NONO, a.k.a.…”
Section: Introductionmentioning
confidence: 99%